2000
DOI: 10.1046/j.1365-2648.2000.01292.x
|View full text |Cite
|
Sign up to set email alerts
|

The development of competency standards for specialist critical care nurses

Abstract: In defining the contemporary role of the specialist nurse it is necessary to challenge the concept of nursing as merely a combination of skills and knowledge. Nursing must be demonstrated and defined in the context of client care and include the broader notions of professional development and competence. This qualitative study sought to identify the competency standards for nurse specialists in critical care and to articulate the differences between entry-to-practice standards and the advanced practice of spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 12 publications
2
70
0
5
Order By: Relevance
“…Dunn et al, 2000;Lindberg, 2006;Schribante et al, 1996) on this topic. These studies share some findings on competence requirements in intensive and critical care nursing; these include collaboration, professional practice and clinical decision-making (Dunn et al, 2000;Lindberg, 2006;Schribante et al, 1996). The main categories of competence requirements for registered critical care nurses are professional competence, cognitive competence, interpersonal skills and critical care patterns of interaction (Schribante et al, 1996).…”
Section: Background and Literature Reviewmentioning
confidence: 95%
See 3 more Smart Citations
“…Dunn et al, 2000;Lindberg, 2006;Schribante et al, 1996) on this topic. These studies share some findings on competence requirements in intensive and critical care nursing; these include collaboration, professional practice and clinical decision-making (Dunn et al, 2000;Lindberg, 2006;Schribante et al, 1996). The main categories of competence requirements for registered critical care nurses are professional competence, cognitive competence, interpersonal skills and critical care patterns of interaction (Schribante et al, 1996).…”
Section: Background and Literature Reviewmentioning
confidence: 95%
“…Empirical research is also lacking in this field: We found only a few empirical studies (e.g. Dunn et al, 2000;Lindberg, 2006;Schribante et al, 1996) on this topic. These studies share some findings on competence requirements in intensive and critical care nursing; these include collaboration, professional practice and clinical decision-making (Dunn et al, 2000;Lindberg, 2006;Schribante et al, 1996).…”
Section: Background and Literature Reviewmentioning
confidence: 96%
See 2 more Smart Citations
“…For instance, "patients who enjoy effective communication with their nurses tend to be more satisfied with the overall care received, exercise greater adherence to recommended treatment regimens, and seem to make more rapid recoveries with fewer complications" (Irving and Dickson, 2004). A competency in nursing setting is not only a skill and tasks but also includes a nurses' characteristic in order to perform effectively (Dunn et al, 2000).…”
Section: Introductionmentioning
confidence: 99%